IMPROVING STUDENTS’ READING ABILITY THROUGH COMIC MEDIA AT GRADE 2 OF SDN 031 SEBERANG KECAMATAN TEMBILAHAN - Ali Munawar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to improve students’ reading ability at grade 2 of SDN 031 Seberang Kecamatan Tembilahan, Indragiri Hilir. The subject of this study were 11 students. This study was class action research aiming to improve the learning process in the classroom. The approach used in this study was comic media to improve reading ability. The results showed that at meeting 1 of cycle I, the percentage of teachers’ activity during learning was 55% with fairly good category. Then, at meeting 4, it increased to 90% with good category. After that, the percentage of students’ learning activities in meeting 1 of cycle I was 53% with fairly good category and at meeting 4, it increased to 92% with good category. The results of students' reading ability after learning reflection on the clarity indicator were scored 3 with moderate category. Then, the word accuracy indicator was scored 4 with high category, and the sound clarity indicator was scored 4 with high category. Judging from the results of the study of students’ reading ability at grade 2 of SDN 031 Seberang, there was a significant increase compared to the data in cycle I. It was proven that the application of comic media to students' reading ability was very effectively applied.